Direct antigen detection for group A streptococcal pharyngitis: comparison of throat cultures and the direct antigen test [A grubu streptokok farenjitlerinde direkt antijen saptanmasi: boǧaz kültürlerinin direkt antijen testi ile karşilaştirilmasi.] - (:unkn) unknown (My University, 1988)
In this study, traditional throat culture results and direct antigen detection from throat swabs have been compared with respect to diagnosis of Group A Beta hemolytic streptococcal infections in children with acute pharyngitis who admitted to Marmara University Hospital Pediatrics Department. It has been found that direct antigen test has a sensitivity of 92% and specificity of 98%.